Synthesis of a Macrocyclic Ligand, Ph4-[14]-Tetraene-N4 and its Metal Complexes with Chromium-, Iron-, Cobalt-and Nickel(II) - Rai, H.C.; Kumar, A.; Kumari, Anuradha (Asian Journal of Chemistry, 2010)
A series of metal complexes of chromium-, iron-, cobalt- and nickel(II) with a macrocyclic ligand 6,7,13,14-Ph4-[14]-6,7,12,14-tetraene-1,5,8,12- N4 has been prepared and characterized on the basis of infrared, electronic, NMR spectral studies as well as conductivity and magnetic moment studies. The ligand reacts with metal(II) salts under conditions of nonaqueous chelation to give macrocyclic complex M(Ph4-[l4]-tetraene- N4)X2 [M = Co(II), Ni(II), Fe(II), Cr(II); X = Cl-, NO3-, OAc- ].